Landscape of Migration : Mobility and Environmental Change on Bolivia's Tropical Frontier, 1952 to the Present - Nobbs-Thiessen, Ben (Book collections on Project MUSE., 2020)
"In the wake of a 1952 revolution, leaders of Bolivia's National Revolutionary Movement (MNR) embarked on a program of internal colonization known as the "March to the East." They encouraged hundreds of thousands of Indigenous Bolivians to relocate from the "overcrowded" Andes to the tropical lowlands, but also welcomed surprising transnational migrant streams, including horse-and-buggy Mennonites from Mexico and displaced Okinawans from across the Pacific. Ben Nobbs-Thiessen details the multifaceted results of these migrations on the environment of the South American interior"--